Cash IS king! – Securing liquidity in economic crisis - Hans Olaf Warning; Michael Grömling; Arne Schulke (IU Internationale Hochschule, 2023)
The beginning of the year 2023 is marked by continued economic instability, some of it still lingering from economic ramifications of the COVID-19 pandemic, some brought on by the war in Ukraine, high energy prices and other more regional factors. For businesses of all shapes and sizes, this poses major challenges in terms of predicting demand, managing performance and supply chains, and ensuring financial stability at the same time - in an environment of steeply declining interest rates and a looming shortage of credit supply. In four parts grouped along the supply chain and the inverse chain of cash movements within a company, this paper seeks to make a case for the importance of liquidity management as a general management discipline rather than a specialized Accounting function. It promotes a broader understanding of the discipline and its rooting in a cross-functional manner in the hearts and minds of managerial staff throughout the entire organization.
Keywords: M10; M19; R41; 650; Working capital; cash management; liquidity expansion